The effectiveness of thinking–based blended learning in developing female Saudi EFL teachers’ pedagogical knowledge and performance - Alwehaibi, Huda (Advances in Social Sciences Research Journal, 2014)
Blended learning, combining face-to-face and online learning, is a promising practice with potential to benefit diverse learners, including teachers themselves. The present study investigates the effectiveness of a thinking based blended learning pedagogy in a TEFL teacher training program. A quasi-experimental one-group pre-test/post-test design was adopted: a sample population of 21 in-service EFL teachers was trained in this model by the author, face to face, for 24 hours over six weeks, with an additional three to four hours of study online and one or two hours of portfolio tasks for each of five modules: Classroom Management, Presentation and Practice, Lesson Planning, Communication Skills, and Memorable Learning. The skills of teaching for thinking were simultaneously incorporated in the training sessions to train teachers on the use of specific instructional strategies that stimulate the students’ thinking. A pedagogical knowledge pre-test/post-test and a classroom observation checklist assessing enhancement of learning were administered. The results show a significantly positive effect on both knowledge and performance, indicating that a well-structured blended learning–based program is an effective tool for teachers’ professional development.